(untitled) (Papeles, 2009)
This paper summarizes the development of an investigation on the incidence of the aspects related to the State Power, and his establishment by means of the speeches recognized by the society as true and resolved from the juridical field, in the participation of the movements of indigenous populations before the National Constituent Assembly of 1991, which aim was identifying the strategies and actions that were developed for the creation of a juridical exceptional aspect for the Indigenous Peoples in all that the juridical unimputability from the western jurisprudence, leaving the device and the juridical processes exclusively to the indigenous traditions and knowledge. This paper focuses, then, on the investigation realized on problematic related to power, social movements, forms of speech and the alternatives present within a system to modify or revert conditions that turn out to be exclusive or opposite to the needs and interests of the population minorities.